2021
DOI: 10.1017/s1368980021004882
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and social inequalities in child malnutrition: nationwide estimates from Brazil’s food and nutrition surveillance system, 2009–2017

Abstract: Objective: In Brazil, national estimates of childhood malnutrition have not been updated since 2006. The use of health information systems is an important complementary data source for analysing time trends on health and nutrition. This study aimed to examine temporal trends and sociodemographic inequalities in the prevalence of malnutrition in children attending primary health care services between 2009 and 2017. Design: Time trends study based on data from Brazil’s Food and Nutrition S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
4
2
1
Order By: Relevance
“…Concerning stunting’s prevalence, our findings (8.4%) were lower than the global data reported by UNICEF (22%) [ 11 ], the Regions of the Americas (8.9%) [ 11 ], the Western Pacific Region (9.3%) [ 11 ], Peru (14.4%) [ 65 ], and Brazil (12.7%) [ 66 ], and higher than the estimate prevalence reported in the European Region (5.7%) [ 11 ]. Reporting the underweight prevalence, our findings (0.5%) were lower than the global data reported by UNICEF (12.6%) [ 11 ], East Asia and Pacific region (5.18%) [ 11 ], and the Regions of the Americas (2.5%) [ 11 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Concerning stunting’s prevalence, our findings (8.4%) were lower than the global data reported by UNICEF (22%) [ 11 ], the Regions of the Americas (8.9%) [ 11 ], the Western Pacific Region (9.3%) [ 11 ], Peru (14.4%) [ 65 ], and Brazil (12.7%) [ 66 ], and higher than the estimate prevalence reported in the European Region (5.7%) [ 11 ]. Reporting the underweight prevalence, our findings (0.5%) were lower than the global data reported by UNICEF (12.6%) [ 11 ], East Asia and Pacific region (5.18%) [ 11 ], and the Regions of the Americas (2.5%) [ 11 ].…”
Section: Discussioncontrasting
confidence: 75%
“…The prevalence of overweight was stable between 1974 and 2006 12 and increased between 2009 and 2017. 13 In our study, although we found little increase in BMI trajectories among children born after 2000, the prevalence of overweight and obesity remained high and further increased during a short period, especially for children aged 5–10. Given the current high prevalence of overweight and obesity, it is important to continue monitoring Brazilian children’s growth.…”
Section: Discussioncontrasting
confidence: 63%
“… 12 A small increase from 11.6% in 2009 to 12.6% in 2017 was found from the Food and Nutrition Surveillance System in Brazil. 13 …”
Section: Introductionmentioning
confidence: 99%
“…A study of temporal trends based on data from SISVAN showed that among children from more vulnerable subgroups (blacks, beneficiaries of conditional cash transfers and residents of undeserved areas), the trend toward a higher prevalence of stunting persists. 24 …”
Section: Resultsmentioning
confidence: 99%